2013
DOI: 10.1016/j.jcrs.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser–assisted small-aperture corneal inlay implantation for corneal compensation of presbyopia: Two-year follow-up

Abstract: Acufocus Inc., Irvine, California, USA, financially supports the Research Foundation for Promoting Ophthalmology, Salzburg, Austria, as the clinical research center of the University Eye Clinic (Paracelsus Medical University). Dr. Grabner received travel expenses from Acufocus, Inc. Dr. Riha currently also works as a clinical application specialist for Acufocus, Inc. No other author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 17 publications
0
58
1
Order By: Relevance
“…Similar results have been observed in previous studies. 6,7 Decrease of luminance was related to deterioration of CS. 26,27 Pupil or pinhole size has a large effect on the optical transfer function of the eye, and if the pupil or pinhole size is fixed, transfer rate decreases more as frequency increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been observed in previous studies. 6,7 Decrease of luminance was related to deterioration of CS. 26,27 Pupil or pinhole size has a large effect on the optical transfer function of the eye, and if the pupil or pinhole size is fixed, transfer rate decreases more as frequency increases.…”
Section: Discussionmentioning
confidence: 99%
“…23 These effects of pinhole glasses can support presbyopia, and this concept led to the development of a small-aperture corneal inlay. [5][6][7] Image quality increased by a pinhole can be diminished when the level of illumination reaching the retina is attenuated. 24 In this situation, pinhole glasses with a series of equally sized, regularly placed pinholes are better than a single pinhole occluder.…”
Section: Discussionmentioning
confidence: 99%
“…19,26 The explantation rate in cases of visual dissatisfaction varies widely across series from 0% to 21%. 14,22,[27][28][29] One study concluded that after removal, corneal topography and aberrometry were not permanently affected with a return to preoperative corrected and uncorrected vision in the majority of cases. 30 Advances in the biocompatibility of materials and designs allowing for improved metabolic regulation have made modern inlays much safer than their precursors.…”
Section: ' Postoperative Complicationsmentioning
confidence: 99%
“…The KAMRA ® inlay (AcuFocus Inc., Irvine, CA, USA), a small-aperture intra-corneal inlay medical device aiming at correcting presbyopia, can be monocularly implanted into a lamellar pocket in the nondominant eye of a patient. Its mechanism of action is to restrict unfocused peripheral light rays to provide increased depth of focus and an extended range of continuous vision expanding from near to far [8,9].…”
Section: Introductionmentioning
confidence: 99%